The impact of hybrid intercultural intervention sprint (HIIS) on developing intercultural competence of adult business learners in Slovenia - Buko, Svitlana (Mednarodno inovativno poslovanje, 2023)
This paper presents research about the impact of a hybrid intercultural intervention sprint (HIIS) on the development of intercultural competencies in a group of Slovenian adult learners enrolled in a graduate-level MA business program. The study used a sequential design, with quantitative data collected both before (N=40) and after (N=36) the short sprint. The HIIS consisted of innovative hybrid learning activities implemented in the form of inventive case-based learning, that took place January-February 2023. The study utilized the VALUE rubric, a survey instrument that measures attitudes, values, and knowledge related to intercultural competencies, with 14 items on a Likert scale. The sequential design of the study allowed for a comparison of intercultural competencies before and after the learning.
Keywords: business adult learners; case-based learning; hibridni intervencijski program; hybrid intervention; intercultural competence; Medkulturna komunikacija; medkulturne kompetence; odrasli učenci poslovnih ved; učenje na podlagi primerov